English as a foreign language learners’ strategy awareness across proficiency levels from the perspective of self-regulated learning metafactors - Habók, Anita; Magyar, Andrea; Molnár, Gyöngyvér (Frontiers in Psychology, 2022)
The previous three decades have seen a growing body of research into language learners’ self-regulated learning (SRL), language learning strategy (LLS) use and their possible effects on proficiency. This study thus provides insights into the relationship between elementary and low intermediate learners’ perceptions of their self-regulated strategy use in English as a foreign language (EFL) and their attitude to English in relation to their proficiency level. Nine hundred and sixty-six higher proficiency students and 399 lower proficiency students in Year 8 participated in the research. A revised Self-Regulated Foreign Language Learning Strategy Questionnaire (SRFLLSQ), a version of Oxford’s Strategy Inventory for Language Learning (SILL), was completed by the participants. Our findings shed light on higher proficiency learners’ significantly higher level of strategy use. Learners at higher levels relied more strongly on their metacognitive strategies, such as planning, organising and monitoring their cognitive processes. Our analysis also showed a high correlation between the different factors of metastrategy use (metacognitive, meta-affective, metasocial and metamotivational) and cognitive, affective, social and motivational strategy use in relation to attitude and proficiency. A path analysis also reinforced our assumption that metafactors significantly determine learners’ proficiency across strategy use and attitude in both higher and lower-level students. The positive contribution of the metastrategies on their corresponding regulated strategy fields appeared to be robust, thus underlining recent LLS research that emphasises the role of metafactors in the language learning process.